Pengaruh Pelatihan Kerja dan Penempatan Karyawan terhadap Produktivitas Kerja Karyawan pada PT. Golden Utama Sejahtera Kabupaten Kediri - Umi Aulia Hardiana; Ahmad Jauhari; Nur Hidayati (Jurnal Riset dan Inovasi Manajemen, 2023)
This research aims to examine the effect of job training and employee placement on work productivity. The analysis techniques used are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis t test and F test, and coefficient of determination test (R2) using the SPSS version 25 program. Results This research shows that the job training variable has a partial effect on work productivity. It is known from the results of the job training t test that the sig. = 0.003 > 0.05 and the employee placement variable has a partial effect on work productivity, this is known from the results of the recruitment t test with a sig value. = 0.005 > 0.05. Meanwhile, the results of research on job training and employee placement have a simultaneous effect on work productivity, this is known from the F test, the sig value. = 0.000 < 0.05